Biomechanical Comparison of a First- and a Second-Generation All-Soft Suture Glenoid Anchor. Issue 7 (20th July 2017) - Erickson, John; Chiarappa, Frank; Haskel, Jonathan; Rice, Justin; Hyatt, Adam; Monica, James; Dhawan, Aman
Background: All–soft tissue suture anchors provide advantages of decreased removal of bone and decreased glenoid volume occupied compared with traditional tap or screw-in suture anchors. Previous published data have led to biomechanical concerns with the use of first-generation all-soft suture anchors. Purpose/Hypothesis: The purpose of this study was to evaluate the load to 2-mm displacement and ultimate load to failure of a second-generation all-soft suture anchor, compared with a first-generation anchor and a traditional PEEK (polyether ether ketone) anchor. The null hypothesis was that the newer second-generation anchor will demonstrate no difference in loads to 2-mm displacement after cycling compared with first-generation all-soft suture anchors. Study Design: Controlled laboratory study. Methods: Twenty human cadaveric glenoids were utilized to create 97 total suture anchor sites, and 1 of 3 anchors were randomized and placed into each site: (1) first-generation all-soft suture anchor (Juggerknot; Biomet), (2) second-generation all-soft suture anchor (Suturefix; Smith & Nephew), and (3) a control PEEK anchor (Bioraptor; Smith & Nephew). After initial cyclic loading, load to 2 mm of displacement and ultimate load to failure were measured for each anchor. Results: After cyclic loading, the load to 2-mm displacement was significantly less in first-generation anchors compared with controls ( P < .01). However, the load to 2-mm displacement was significantly greater in second-generation anchors compared with controls ( P < .01). There was no difference in ultimate load to failure between the first- and second-generation all-soft suture anchors ( P > .05). Conclusion: The newer generation all-soft suture anchors with a theoretically more rigid construct and deployment configuration demonstrate biomechanical characteristics (specifically, with load to 2-mm displacement after cyclic loading) that are improved over first-generation all-soft suture anchors and similar to a traditional solid tap-in anchor. The configuration of these newer generation all-soft suture anchors appears to mitigate the biomechanical concerns of decreased load to failure with first-generation all–soft tissue suture anchors. Clinical Relevance: The theoretical advantages of all-soft anchors may be particularly valuable in revision surgery or in cases where multiple anchors are being placed into a small anatomic area.